West Lombok Towards Smart Government (Case Study of E-Government Implementation at the Population and Civil Registration Services Office) - R. Luki Karunia (Political Science Program, Universitas Negeri Semarang, 2023)
This study aims to evaluate the implementation of smart government in West Lombok Regency, West Nusa Tenggara. The research was conducted on the population and civil registration services by looking at four aspects: an overview of the use of information technology-based applications used, public services performed, an overview of the bureaucracy and public policies, and explaining the factors that hinder the ineffectiveness of smart government. The method used is a qualitative research method. Data collection was carried out through interviews, document review, and observation. The results showed that implementing smart government at the Population and Civil Registry Office of West Lombok district from public service indicators needed to have been more effective. There still needs to be an increase in facilities and infrastructure, especially computers, scanners, adding internet networks in each service room. The policy aspect is also not practical because people are not aware of the policy's existence because many people do not have smartphones and do not understand technology. In addition, online socialization needs to be massively encouraged. Lack of budget from APBD funds resulting in limitations in buying facilities and infrastructure that support smart government.